Effectiveness of procurement auditing conducted by FAPAD in ensuring accountability: a case study on a selected foreign aided project - Rahman, Khan Md. Ferdausur (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.